Leveraging Predictive Analytics for Resource Optimization in Non-Profit Organizations - , Sesan Omojola, Kenechi Okeke (Archives of Current Research International, 2025)
Aim: This study explores the use of predictive analytics for optimizing resource management and operational efficiency within non-profit organizations (NPOs) with a focus on recent trends in technology developments. Study Design: A comprehensive review of literature in relation to the use of predictive analytics within the non-profit organization sector, especially between 2020 and 2025, with a focus on data-driven decision-making and improvement frameworks. Methodology: The review adopted a systematic literature review approach, gathering articles from peer-reviewed journals like Google Scholar, Scopus, SSRN, and Business Source Complete. Results: The study integrated knowledge from 15 recent papers to show that predictive analytics improves the efficiency of fundraising, volunteer management, beneficiary targeting, and allocation of inventory. Technologies like machine learning algorithms, regression models, and time-series forecasting significantly contribute to forecasting donor behavior, demand cycles, and operational constraints. Implementation challenges including data privacy concerns, algorithmic bias risks, and organizational capacity limitations were consistently identified across studies. Conclusions: Predictive analytics presents a transformative opportunity for non-profits to maximize the use of limited resources. However, challenges such as data quality, organizational capacity, ethical considerations around data use, and appropriate governance frameworks require tailored approaches to maximize the potential of analytics in the non-profit environment.